MARKET REACTION TO BI7DRR FLUCTUATIONS (EVENT STUDY ON LQ45 STOCK INDEX) - Fajri Mas Afifah; Made Reina Candradewi; Ni Putu Santi Suryantini; Luh Gede Sri Artini (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2025)
Market reaction shows how investors respond to information, which affects the stock price and trading volume. Analyzing market reaction is important for companies and investors. The BI7DRR policy is important information that causes a reaction in the stock market. The published information is part of the efficient market in semi-strong form, which was examined by the event study. This study aims to examine the market reaction using average abnormal return and average trading volume activity. The research sample consists of 23 companies, which continuously listed on LQ45 Stock Index, selected using purposive sampling. To examine the hypotheses, this study uses the Paired Sample T-Test and the Wilcoxon Signed Rank Test. The research found a difference in average abnormal return before and after BI7DRR interest rate cut, while the average trading volume activity showed no difference before and after the event. Conversely, the market reaction test during the interest rate hike shows a difference in the average abnormal return and the average trading volume activity before and after the event. These conditions indicate that the stock market reacted significantly to the information and was inefficient in semi-strong form.